2011
DOI: 10.1103/physreva.84.032703
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic theory of the double photoionization of heliumlike atoms

Abstract: A fully relativistic calculation of the double photoionization of heliumlike atoms is presented. The approach is based on the partial-wave representation of the Dirac continuum states and accounts for the retardation in the electron-electron interaction as well as the higher-order multipoles of the absorbed photon. The electron-electron interaction is taken into account to the leading order of the perturbation theory. The relativistic effects are shown to become prominent already for the medium-Z ions, changin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 44 publications
2
23
1
Order By: Relevance
“…This explains why we took great care in order to calculate σ ++ and σ + fully consistently, i.e., both to the leading order in perturbation theory with exactly the same screening potential in the Dirac equation (7). Importance of such consistency was implicitly acknowledged already in previous perturbation-theory calculations [15,22,23], where results were presented solely in terms of R, and not in terms of σ ++ . From the comparison in Tables I-III, we see that the difference between the CH 1 and CH 2 results (which we use for estimating the magnitude of the residual electron correlation effects) monotonically decreases with the increase of the nuclear charge.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…This explains why we took great care in order to calculate σ ++ and σ + fully consistently, i.e., both to the leading order in perturbation theory with exactly the same screening potential in the Dirac equation (7). Importance of such consistency was implicitly acknowledged already in previous perturbation-theory calculations [15,22,23], where results were presented solely in terms of R, and not in terms of σ ++ . From the comparison in Tables I-III, we see that the difference between the CH 1 and CH 2 results (which we use for estimating the magnitude of the residual electron correlation effects) monotonically decreases with the increase of the nuclear charge.…”
Section: Resultsmentioning
confidence: 88%
“…The prefactor of Z 2 in the definition (10) ensures that the function R(ω/ω cr ) depend only weakly on the nuclear charge and the degree of ionization of atom (ion); this fact is often termed as the universal scaling law of double photoionization [26,27]. In our previous calculation for He-like ions [15], we demonstrated that this scaling holds exactly in the nonrelativistic limit and to the first order in perturbation theory, but is violated by the relativistic effects.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations